I’ve attached a photo with my work ....
Hope it helps!!
P(x) = x^4 - 9x^2 - 4x + 12
P(1) = 1^4 - 9(1)^2 - 4(1) + 12 = 1 - 9 - 4 + 12 = 0
x = 1 is a root.
By dividing the polynomial by x - 1, gives other roots as 3 and -2
let's recall the graph of sin(x), is simply a sinusoidal line waving about, but its midline is at the x-axis, namely y = 0.
this equation is simply a transformation of it, the 1/2 changes the amplitude by half, midline stays the same though, the +3, moves the whole thing upwards, a vertical shift of 3, meaning the midline went from 0 to 3, y = 3.
25 minutes (0:25) added to 7:15.
7:15 + 0:25 = 7:40
Also expressible as 15+25
He arrived at 7:40AM.
Area of one square = 2 x 2 = 4 square feet
4 square feet x 6 squares = 24 square feet total area
Answer: 24 square feet